2022
DOI: 10.3390/ijerph191811395
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Internal Structure Type of a Large-Area Lower Exhaust Workbench on Its Surface Air Distribution

Abstract: Local exhaust ventilation is an important method of contamination control, and the type of exhaust hood and the air distribution at the hood face have an important influence on the contamination control effect. When the hood face is large, it is difficult to create a uniform airflow distribution at the hood face, which if achieved, could improve the effect of contamination control. To that end, the large-area workbench used in the process of vaccine purification was taken as the research subject prototype for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Therefore, the installation of the rectifier orifice plate was required to accomplish the equal distribution of wind velocity, temperature, and humidity. The regularity of air flow may be significantly improved using rectifier orifice plates, according to studies [18,19]. Ingeniously, this invention suggests combining a heating tube with a rectifier orifice plate to simultaneously heat and correct the air flow.…”
Section: Physical Modelmentioning
confidence: 99%
“…Therefore, the installation of the rectifier orifice plate was required to accomplish the equal distribution of wind velocity, temperature, and humidity. The regularity of air flow may be significantly improved using rectifier orifice plates, according to studies [18,19]. Ingeniously, this invention suggests combining a heating tube with a rectifier orifice plate to simultaneously heat and correct the air flow.…”
Section: Physical Modelmentioning
confidence: 99%
“…In recent years, there has been an increase in the use of femtosecond laser processing technology in the bulk processing, surface microstructure processing, and surface modification of various materials, including metal materials. This is due to its unique machining mechanism, with high-quality machining results that can be used for the machining of non−metallic organic materials [10][11][12], polymeric substances [13], and semiconductor materials [14], and excellent properties such as high machining accuracy [15][16][17]. Due to the femtosecond laser machining technique's extremely high spatial resolution, femtosecond laser machining of diamond and other super-hard materials has great efficiency, good processing quality, and high flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…However, these designs must be completed prior to the construction of the plant factories. For existing plant factories, it is evident that the location of the vents and the lack of monitoring and verification of the actual airflow field cannot be changed [22,23]. Kozai et al concluded that LED heat dissipation affects the uniformity of the airflow field, particularly in the case of different light source arrangements in the plant factories [24].…”
Section: Introductionmentioning
confidence: 99%